PENGARUH VARIABEL MAKRO EKONOMI TERHADAP TABUNGAN NASIONAL DI INDONESIA - Diah Okta Ayunigtiyas (Jurnal Ekonomi Pembangunan, 2009)
This research aim to know the influence of macro economics variables to national saving in Indonesia and also most dominant influence to national saving in Indonesia. Method which is used in this research is double linear regression Partial Adjustement Model used for perceiving short-range and long-range responsivenees from dependent variable to one changed unit of independent variable value. From result of examination obtained real rate of interest and previous period of the national saving individually having influence significantly to the level of national saving. The influence variable to the level of national saving is the level of previous period national saving model because analysis model that used is adjustment of partial model. Outside independent variable, in the reality variable that influencing to the level of national saving is national income.